Reasoning with statistics : how to read quantitative research - Williams, Frederick (New York : Holt, Rinehart, and Winston, 1986)
This book is intended for people who wish to be knowledgeable readers of quantitative research literature in their field but who lack the necessary statistical background.
includes illustrations
Includes bibliographies and index.
ijb, 15/01/2019
Loans
Keywords: Research; Social sciences